Contratos coligados e a exceção do contrato não cumprido - Guimarães, Luciano Cezar Vernalha (2018)
The related contracts may be considered a new modality of contractual arrangement, with own particularities and peculiarities. The traditional studies of contract, despite providing the theoretical framework for the legal treatment of related contracts, does not account for disciplining all the potentialities associated with this type of contracting. The doctrine, therefore, has looked over the subject, in order to produce material capable of conceptualizing, systematizing and classifying the related contracts. In this context, it becomes relevant the verification of legal consequences of related contracts. Among the consequences, it is important here to deal with exception non adimpleti contractus. The purpose is to establish criteria and parameters for the application of the exceptio non adimpleti contractus in the related contracts